Implementasi Metode Dan Evaluasi Pembelajaran Di Pondok Pesantren Jareqje Pambusuang Kabupaten Polewali Mandar - Inwan, mi'raj (Al-Riwayah : Jurnal Kependidikan, 2024)
The implementation of teaching methods must align with educational objectives, the material taught, and evaluation tools to measure teacher effectiveness and student success. This study aims to analyze the teaching methods at Pondok Pesantren Jareqje Pambusuang, which integrate traditional (salafi) and modern (khalafi) approaches. The research method used is descriptive qualitative, involving observation, interviews, and document analysis. The results show that the sorogan, bandongan, and outdoor learning methods enhance active student engagement and collaboration, which are essential for optimal learning outcomes. A supportive learning environment also plays a role in influencing student interest and engagement. Evaluation is comprehensively conducted through diagnostic, formative, and summative assessments that evaluate both academic abilities and character development of the students. The implications of this research suggest professional development for educators, the integration of technology in teaching, and health programs to improve the effectiveness of learning and student well-being.